2001
DOI: 10.2307/3761750
|View full text |Cite
|
Sign up to set email alerts
|

Field Observations and Inoculation Experiments to Determine the Nature of the Carpophoroids Associated with Entoloma abortivum and Armillaria

Abstract: Carpophoroids traditionally attributed to Entoloma abortivum ("Aborted Entolomas") represent malformed Armillaria fruiting bodies permeated by E. abortivum hyphae, as shown by our field observations and preliminary laboratory work. This contradicts the generally accepted hypothesis that carpophoroids are E. abortivum fruiting bodies colonized by Armillaria. Carpophoroids possess many of the structural characteristics of Armillaria fruiting bodies, including growth and development from rhizomorphs and the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…The formation of carpophoroids associated with species of E. abortivum have traditionally been thought to be the result of an Armillaria species attacking and parasitizing Entoloma sporocarps (11), a conclusion drawn based on the fact that Armillaria species are wide-spread forest pathogens (12). However, subsequent studies have shown the opposite: the production of carpophoroids are the result of E. abortivum disrupting the development of Armillaria sporocarps (14). Here, we employed RNA sequencing and differential gene expression analysis on field-collected fungal tissue of each of the three components of this association to better understand the mechanistic basis of this interaction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The formation of carpophoroids associated with species of E. abortivum have traditionally been thought to be the result of an Armillaria species attacking and parasitizing Entoloma sporocarps (11), a conclusion drawn based on the fact that Armillaria species are wide-spread forest pathogens (12). However, subsequent studies have shown the opposite: the production of carpophoroids are the result of E. abortivum disrupting the development of Armillaria sporocarps (14). Here, we employed RNA sequencing and differential gene expression analysis on field-collected fungal tissue of each of the three components of this association to better understand the mechanistic basis of this interaction.…”
Section: Discussionmentioning
confidence: 99%
“…8B). Armillaria mellea has previously been identified as a host of E. abortivum (11,14), but this interaction does not appear specific to just A. mellea. Interestingly, Armillaria species parasitized by E. abortivum appear to be only those present in Eastern North America and Asia (14,37,55).…”
Section: Identity Of Armillaria Species In This Interaction Phylogenomic Analysis Of Thementioning
confidence: 96%
See 2 more Smart Citations
“…Armillaria species in east Asia engage in a form of mycorrhizal relationship known as mycoheterotrophy with species of achlorophyllus orchids in the genera Galeola and Gastrodia (Kikuchi & Yamaji, 2010; Guo et al, 2016). In other examples, Armillaria sporocarps are parasitized by the mushroom-forming species Entoloma abortivum (Lindner Czederpiltz et al, 2001; Koch & Herr, 2021) and potentially also by species in the Ascomycete genus Wynnea (Xu et al, 2019). Lastly, Guyanagaster necrorhizus harbors nitrogen-fixing bacterial species within its sporocarps, which likely facilitates a dispersal mutualism with wood-feeding termites (Koch et al, 2018; Koch et al, 2021).…”
Section: Introductionmentioning
confidence: 99%